Promoting Work Motivation and Creating A Conductive Work Environment To Improve Employee Performance At PT Nion Monita Food Indonesia - Ana Alfiah Nur Zanah; Noveria Susijawati (Rescollacom (Research Collaborations Community), 2026)
This study aims to analyze the effect of work motivation and work environment on employee performance at PT Nion Monita Food Indonesia. This study uses a quantitative approach with a survey method of 109 employees who have worked for at least one year. The sampling technique used purposive sampling. Data were collected through a questionnaire with a five-point Likert scale and analyzed using multiple linear regression through the SPSS program. The results show that work motivation has a positive and significant effect on employee performance (β = 0.561; t = 6.132; p < 0.001). The work environment also has a positive and significant effect on employee performance (β = 0.318; t = 3.476; p = 0.001). Simultaneously, work motivation and work environment were able to explain 70.8% of the variation in employee performance (Adjusted R² = 0.708; F = 128.470; p < 0.001). These findings indicate that increasing work motivation supported by a conducive, comfortable, and safe work environment can optimally improve employee performance.